Chemical diversity, anti-inflamimmatory and anti-cancer activities of secondary metabolites in soft corals from Tun Sakaran Marine Park, Sabah - Intan Irna Zanil (2015)
Soft corals (Cnidaria, Anthozoa, Octocorallia) are prolific producers of bioactive cembranoid diterpenes and steroids. North Borneon waters of Malaysia are rich with diverse species of soft corals but few have been investigated and documented. Present investigation delves upon the chemical constituents of three soft corals; Sinularia spp., Lobophytum spp. and Sarcophyton spp. from Tun Sakaran Marine Park (Sabah, Malaysia). Crude hexane and 90 % MeOH extracts were obtained and subjected to Thin Layer Chromatography (TLC) and High Performance Liquid Chromatography (HPLC) profiling. Secondary metabolites were isolated based on the chemical profiles and purified using repetitive Preparative Thick Layer Chromatography (PTLC). As a result, a total of eight diterpenes were isolated and their structures determined via spectroscopic techniques. Briefly, Sarcophyton spp. produced two iso-propyl(ene) type cembrane diterpenes; 1R, 4R, 2E, 7E, 11E)-cembra- 2,7,11-trien-4-ol (7) (5.8%) and 8 (2.5%). Additionally, Sinularia spp. produced (E, E, E)-6,10,14-trimethyl-3-methylene-cis-3a, 4,5,8,9,12,13,15-octahydrocyclotetradeca[ b]furan-2(3H)-one (1) (16.7%), 2 (5.0 %), denticulatolide (3) (4.5%) and 4 (4.5%) while Lobophytum spp. produced cembranolide A (5) (7.26%) and (9E,1 3E)-5-acetoxy-6-acetyl-9,13-dimethyl-3-methylene-34,3,5a,,6 ,12,8,1,12,14adecahydro- 2H-cyclotetrideca-(b)furan-2-o(n6e) (16.2%). These six compounds are cembranoid diterpenes containing a-methylene y lactones functional group. Of the eight compounds, 2,4 and 8 were identified as new compounds while the remaining five compounds are known. Compounds were tested for biological activities using cell based assays; 1) anti-inflammation (LPS-stimulated RAW 264.7 macrophage), and 2) anti-cancer (human promyelocytic leukemia cells - HL-60). Cembrane diterpenoids with lactone functionality showed potent activities against both cell based assays. At the concentration of 12.5 and 25.0 μg/ml, compound 3, 4,5 and 6 were found to significantly inhibit the production of nitric oxide (NO), IL-1ß and IL-6 by suppressing the production of iNOS protein in the LPS-stimulated RAW 264.7 macrophage. In addition, these compounds also mildly inhibited PGEZ production at the same concentration by blocking the accumulation of COX-2 protein in the cells. On the other hand, at the same concentration, compound 1 and 2 showed weak activity when tested against the LPS-stimulated RAW 264.7 macrophage. At the concentration of 25 μg/ml, an MTT assay showed that compound 3,4 and 6 exhibited potent cytotoxic activity against HL-60 cancer cells, while compound 1,2 and 5 are weakly cytotoxic against the same cell line. Furthermore, as the cancer cells were treated with the increasing concentration of compound 3,4 and 6 (12.5,25,50 μg/ml), the expression level of Bax and cleaved caspase-3w ere increased while the expression level of BCI-xl were decreased. Thus, it showed that these compounds also give apoptosis-induced effects on the cancer cells. This investigation is a new study on the chemical diversity and biology potential of soft corals in Tun Sakaran Marine Park.